Pengaruh Sikap Nasionalisme Pemuda terhadap Keamanan di Kota Bandung (Studi pada Siswa SMUN 3 dan SMUN 5 Bandung) - Iriansyah, Mochammad Nurdi; Sumadinata, Widya Setiabudi; Djuyandi, Yusa (Jurnal Analisis Sosial Politik, 2020)
Indonesia is an archipelagic country, of course, with the many islands owned by the Indonesian people, Indonesia is rich in natural resources and also rich in ethnic, religious and cultural diversity. Wealth, in turn, has an impact on the emergence of threats in people's lives in the form of conflicts and if this continues, it is one of the signs that Indonesian nationalism, especially in Bandung, is experiencing a threat and of course it will have an impact on security. This study uses an attitude theory approach, nationalism theory and security. This research method is quantitative with a questionnaire measuring instrument that is prepared based on research indicators sourced from research variables. The data analysis used simple linear regression analysis with the result that there was an influence of youth nationalism attitudes towards security with a contribution of 44%. From these results it can be concluded that there is indeed an effect of nationalism on security where the lower the attitude of nationalism, the lower the security in the city of Bandung, and vice versa.